An evaluation of C and N on fresh and aged crop residue from mixed long-term no-till cropping systems. (20th January 2017) - Aher, G.; Cihacek, L. J.; Cooper, K.
ABSTRACT: Conservation crop residue management increases soil organic carbon (SOC) storage, nutrient cycling and availability and improves soil quality. This study was conducted to evaluate the amount of residue biomass, residue carbon to nitrogen (C:N) ratio, residue carbon (C) and nitrogen (N), and residue N fertilizer deficit (supplemental N fertilizer requirement) from crop residue decomposition in long-term no-till production. Aboveground aged and fresh residues were collected in spring 2011 and fall 2012, respectively. Results showed slightly greater residue dry matter weight in aged residue than fresh residue. C:N ratios were wider in fresh residue than the aged residue. Both aged and fresh residue also showed wider C:N ratio in the corn ( Zea mays L.)-soybean ( Glycine max L.) rotation (66.6 and 64.4, respectively) and narrower C:N ratio in the spring wheat ( Triticum aestivum L.)-winter wheat ( Triticum aestivum L.)-alfalfa ( Medicago sativa L.)-alfalfa-corn ( Zea mays L.)-soybean ( Glycine max L.) (45.6 and 35.7, respectively). Individual fresh crop residues showed narrower C:N ratios for legume and cover crops than non-legume crops. Analysis of potential supplemental N fertilizer requirements showed greater potential N requirement for the fresh residue than the aged residue.